Visible light photoinitiating systems by charge transfer complexes: Photochemistry without dyes - Garra, Patxi; Fouassier, Jean-Pierre; Lakhdar, Sami; Yagci, Yusuf; Lalevée, Jacques (Elsevier BV, 2020)
Abstract Visible light induced synthesis generally involves i) dyes or chromophores with potential photocleavable bonds (Type I photoinitiator), ii) hydrogen abstractions (Type II photoinitiator) by dyes/chromphores and iii) photoredox catalysis using metal-based or metal-free dyes. Beyond these strategies, charge transfer complexes (CTCs), also referred to as electron donor acceptor (EDA) complexes, were also reported to be the visible light initiating species. In these cases, the ground state intimate association of a donor and acceptor creates a new structure that can result in (bathochromic) visible light absorption compared to the separated compounds. In the present review, an update on CTCs as photoinitiating systems for photopolymerization applications will be provided with examples of CTC-specific structure/reactivity/efficiency relationships. Interestingly, CTC can act as dual photo/thermal photoinitiators both in cationic and free radical photopolymerizations. Also, low optical density of the CTC in resins allowed to access extremely thick samples and composites. The possibility of extending wavelength sensitivity of photopolymerizations by excited state complexes (exciplexes) is also discussed.
Keywords: Photopolymerization; Photochemistry; Dual curing; Photoinitiators; Peroxides; Photoinitiating systems; [CHIM.COOR]Chemical Sciences/Coordination chemistry; Charge transfer complex; Dyes; Visible light; Composites